Welcome to dystopia : forty-five visions of what lies ahead - Van Gelder, Gordon (New York : OR Books LLC, 2019)
"In this diverse and vigorous mix of stories by newcomers and luminaries, writers offer their takes on what life might hold for us in the next few years. The resulting visions of war, oppression, and daily struggle are sometimes humorous, sometimes terrifying (and occasionally both), but always thought-provoking." --
Sneakers / Michael Libling -- re: Your Wedding / Ruth Nestvold -- Everything Is Fixed Now / K. G. Anderson -- His Sweat Like Stars on the Rio Grande / Janis Ian -- Agnosia / J. M. Sidorova -- The Adventure of You / Paul La Farge -- ♋ / N. Lee Wood -- Birds / Deepak Unnikrishnan -- The Only Constant / Leslie Howle -- The Terrific Leader / Harry Turtledove -- Two Explicit and Three Oblique Apologies to My Oldest Daughter One Month Before Her Eighteenth Birthday / Heather Lindsley -- The Levellers / Deji Bryce Olukotun -- No Point Talking / Geoff Ryman -- Glow / J.S. Breukelaar -- Precaution at Penn Station / Michael Kandel -- Newsletter / Jennifer Marie Brissett -- Statues of Limitations / Jay Russell -- Suffocation / Robert Reed -- Application for Asylum / Eileen Gunn -- Welcome to Triumph Band / Yoon Ha Lee -- Loser / Matthew Hughes -- We All Have Hearts of Gold® / Leo Vladimirsky -- Notes on Retrieving a Fallen Banner / Marguerite Reed -- Ticket to Ride / Eric James Fullilove -- Burning Down the House / Ted White -- Dangerous / Lisa Mason -- Class Assignment / Thomas Kaufsek -- Walls / Paul Witcover -- The Passion According to Mike / Scott Bradfield -- Bright Sarasota Where the Circus Lies Dying / James Sallis -- The Name Unspoken / Richard Bowes -- The Elites / Stephanie Feldman -- January 2018 / Barry N. Malzberg -- Farewell / Mary Anne Mohanraj -- The Amazing Transformation of the White House Dog / Ron Goulart -- Handmaid's Other Tale / Jane Yolen -- Sanctuary / Brian Francis Slattery -- One Fell Swoop / James Morrow -- BK Girls / TS Vale -- Isn't Life Great? / Don D'Ammassa -- The Men Will Be Hungry Afterwards / Ray Vukcevich -- The Road South / Madeleine E. Robins and Becca Caccavo -- Skippy's Visit East / Michael Kandel -- Designed for Your Safety / Elizabeth Bourne -- Extreme Bedding / David Marusek.
Description based on print version record.
eBooks on EBSCOhost
Keywords: Dystopias -- Fiction; Science fiction; Short stories; Fantasy fiction; Dystopies -- Romans, nouvelles, etc; Nouvelles; short stories; Dystopias; Fantasy fiction; Science fiction; Short stories; Fiction; Fiction; Romans